PEMODELAN SENYAWA PHALERIN BERTANDA 125I UNTUK UJI ANTIRADANG - Wening Lestari; A Mutalib (Pusbindiklat - LIPI, 2009)
A model of 125I-phalerin was designed in this research. The work was started by designing phalerin based on available data and followed by minimizing energy at bond angles, i.e C4-05-C7-C8 (0 ) , C5-C7-C8-C9 (2),C3-014-C15-C20 (3) and C4-C3-014-C15 (4).This work was then continued with designing of 115l -phalerin. Both models were put in overlaid position, then they were characterized. Result showed that phalerin model has characteristic of bond angle with 1 z 3, 4= 40°, 40°, 320°, 280° respectively. Energy ofphalerin model was 18,7625 kkal/mol.